1931
DOI: 10.1002/zaac.19311950137
|View full text |Cite
|
Sign up to set email alerts
|

Zur Theorie der Rekristallisation

Abstract: 1 l) 2 rs = f lo p A. EUCKEN, Chem. Physik, Leipzig 1930,644. Eine genaue Berechnung von ZI ist unmtiglich, das owohl der Atomabstand als auch der Durchmesser der Wirkungsspharen sich mit der Temperatur andern. Beim Schmelzpunkt wird r,, sich immer mehr r, nahern. welche als Losung ergibt2) : oder da l) J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1931
1931
1974
1974

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Liempt (1931) reported the transition temperature to be 228 °C, although experiments described in this paper indicate that this might be high. The higher density of ~-WCI 6 (Table 1) is also consistent with its being the lower temperature form.…”
Section: +1mentioning
confidence: 65%
See 2 more Smart Citations
“…Liempt (1931) reported the transition temperature to be 228 °C, although experiments described in this paper indicate that this might be high. The higher density of ~-WCI 6 (Table 1) is also consistent with its being the lower temperature form.…”
Section: +1mentioning
confidence: 65%
“…Although a phase change at 228°C had been observed by Liempt (1931), the structure of the second polymorph of WC16 was not investigated until recently (Smith, Landingham, Smith & Johnson, 1968). These authors found a hexagonal polymorph of WC16 with a=10.511 (3) A and c=5.757 (1) A, (Table 1), the cell being similar to that of UCI6 which has the hexagonal space group P3ml and a= 10.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation